Pengaruh Lingkungan Keluarga Dan Religiusitas Terhadap Intensi Berwirausaha - Aulia Hasri; Yuhendri L.V (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
This research aims to analyze the influence of family environment and religiosity on entrepreneurial intensity. This research is included in the category of causal research using a quantitative approach. The population in this study were students at the Faculty of Tourism and Hospitality, Padang State University. The tool used to collect data is a questionnaire. Multiple linear regression is the data analysis technique used in this research. The findings of this research indicate that family environment and religiosity have a significant influence on entrepreneurial intensity. In particular, the family environment has a significant effect on intensity and does not have a significant effect on entrepreneurial intensity. Entrepreneurial tendencies are significantly influenced by the family environment. Meanwhile, religion has little impact on a person's ambition to start a business. This research can be applied to encourage students at FPP UNP to become entrepreneurs.